2021
DOI: 10.1002/qre.2842
|View full text |Cite
|
Sign up to set email alerts
|

Distribution‐free triple EWMA control chart for monitoring the process location using the Wilcoxon rank‐sum statistic with fast initial response feature

Abstract: The exponentially weighted moving average (EWMA) control chart is a memory‐type chart known to be more efficient in detecting small and moderate shifts in the process parameter. The double EWMA (DEWMA) chart is an extension of the EWMA chart that is more effective than the latter in the detection of small‐to‐moderate shifts. This paper proposes a new distribution‐free (or nonparametric) triple EWMA (TEWMA) control chart based on the Wilcoxon rank‐sum (W) statistic to improve the detection ability in the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…39 Initial response features considered here are a power transformation adjustment factor (denoted as FIR adj ) such that when the effect of FIR has completely disappeared, the FIR adj equals 1. According to Steiner, 21 Haq et al, 24 and Letshedi et al, 25 the BFIR, MFIR, and IMFIR features are respectively given by…”
Section: Hwma Monitoring Scheme With Fir Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Initial response features considered here are a power transformation adjustment factor (denoted as FIR adj ) such that when the effect of FIR has completely disappeared, the FIR adj equals 1. According to Steiner, 21 Haq et al, 24 and Letshedi et al, 25 the BFIR, MFIR, and IMFIR features are respectively given by…”
Section: Hwma Monitoring Scheme With Fir Featuresmentioning
confidence: 99%
“…The aforementioned researches and others concluded that FIR features shrink the time‐varying control limits of the CUSUM, EWMA, and GWMA schemes, and therefore, improve their performances in detecting start‐up problems. More recently, Letshedi et al 25 proposed the use of a new improved MFIR feature (denoted as IMFIR) to improve the performance of a single, double and triple EWMA schemes based on the nonparametric Wilcoxon rank‐sum statistic. The IMFIR feature is shown to be more effective than the MFIR and BFIR features in detecting location shifts in a nonparametric setup.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Letshedi et al (2021) proposed a new distribution-free triple EWMA control chart based on the Wilcoxon rank-sum statistic to improve the ability for tracking down plausible changes in location parameter of the underlying distribution. In their framework, a new fast initial response feature is also activated in order to make the resulting chart more efficient.…”
Section: Nonparametric Ewma Control Charts Based On Wilcoxon Rank-sum Statisticmentioning
confidence: 99%
“…In their framework, a new fast initial response feature is also activated in order to make the resulting chart more efficient. Following a similar argumentation as the one established by Alevizakos et al (2020b), Letshedi et al (2021) constructed their triple EWMA scheme based on the following monitoring statistic:…”
Section: Nonparametric Ewma Control Charts Based On Wilcoxon Rank-sum Statisticmentioning
confidence: 99%
“…A well-known nonparametric test is based on the Wilcoxon rank-sum (W) statistic [29]. In the SPM context, control charts based on the W statistic have been studied by Li et al [30], Malela-Majika and Rapoo [31], Mukherjee et al [32], Chong et al [33], Mabude et al [34], Tercero-Gomez et al [35], Triantafyllou [36], and Letshedi et al [37]. Most of the latter articles were studied under the assumption of simple random sampling (SRS) technique.…”
Section: Introductionmentioning
confidence: 99%